Analisis Pengalaman Pembelian Online, Kualitas Layanan dan Kepercayaan Terhadap Kepuasan Konsumen E-commerce Shopee di Kecamatan Giriwoyo Kabupaten Wonogiri - Nurullia Rizkyani; Singgih Purnomo; Esti Dwi Rahmawati (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2024)
Electronic commerce or what is usually called e-commerce is a term used to describe the transaction process for products, services and information carried out using the Internet. With increasingly advanced e-commerce services, consumers can more easily access and order products from various places easily and quickly. This causes many companies to compete to create quality e-commerce services that consumers can trust in order to make things easier and add value to the product or company. This research aims to determine and analyze the influence of online purchasing experience, service quality, and trust on Shopee e-commerce consumer satisfaction in Giriwoyo District, Wonogiri Regency. The population in this research is Shopee e-commerce consumers in Giriwoyo District. This research used purposive sampling as a sampling technique, the number of samples obtained was 100 respondents. The results of this research show that Online Purchasing Experience (X1) has a positive and significant effect on Consumer Satisfaction, Service Quality (X2) has a positive and significant effect on Consumer Satisfaction, Trust (X3) has a positive and significant effect on Consumer Satisfaction, and Experience Online Purchasing, Service Quality and Trust together have a positive and significant effect on Consumer Satisfaction in Giriwoyo District, Wonogiri Regency.